1997
DOI: 10.1095/biolreprod57.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of 4-Tert-Octylphenol to Adult Male Rats Causes Shrinkage of the Testes and Male Accessory Sex Organs, Disrupts Spermatogenesis, and Increases the Incidence of Sperm Deformities1

Abstract: The environmental toxicant 4-tert-octylphenol (OP) has been shown to exert estrogenic effects on mammalian cells in culture. Recent findings from our laboratories demonstrate clearly that OP administration disrupts reproductive hormone secretion in the adult male rat, quite likely as a result of estrogenic action. In the present study, we investigated the impact of these or other OP-induced changes on male reproductive tissues. Adult male rats were injected with OP (20 or 80 mg) or estradiol valerate (EV; 0.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(58 citation statements)
references
References 20 publications
4
54
0
Order By: Relevance
“…NP is a weakly estrogenic compound generated from alkylphenol ethoxylates that is widely used in the production of plastics, textiles, and agricultural chemicals and in household applications and cosmetics [25,29,30]. Several studies have reported the adverse effects of NP on development of the male reproductive tract when animals are parentally exposed to NP [13,31]. Therefore, our results suggest that the inhibition of 3β-HSD mRNA production by NP and OP may be due to functional defects in Leydig cells such as a reduction in cytochrome P450 enzyme production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NP is a weakly estrogenic compound generated from alkylphenol ethoxylates that is widely used in the production of plastics, textiles, and agricultural chemicals and in household applications and cosmetics [25,29,30]. Several studies have reported the adverse effects of NP on development of the male reproductive tract when animals are parentally exposed to NP [13,31]. Therefore, our results suggest that the inhibition of 3β-HSD mRNA production by NP and OP may be due to functional defects in Leydig cells such as a reduction in cytochrome P450 enzyme production.…”
Section: Discussionmentioning
confidence: 99%
“…Octylphenol (OP) exerts estrogenic action to suppress LH, FSH and testosterone secretion and enhance prolactin secretion. OP greatly reduces sperm number and adversely influences the size of the rat testis [13]. Diethylstilbestrol (DES) induces a reduction in testis formation and abnormal semen, resulting in infertility in rats [14,15].…”
mentioning
confidence: 99%
“…Importantly, all these effects were observed only when relatively high doses (400 mg/kg bw) of alkylphenols were used (Atanassova et al, 2000; Sharpe et al, 2003). Administration of high doses of alkylphenols to adult males resulted in reduced size and function of the testis, epididymis and male accessory glands, decreased serum LH, FSH and testosterone concentrations, increased apoptosis of germ cells and reduced sperm count (Blake & Boockfor, 1997;Boockfor & Blake, 1997;Han et al, 2004;Gong & Han, 2006;Kim et al, 2007). However, reports on the effects of lower doses (<200 mg/kg bw) of octylphenol on male reproductive system are contradictory (Bian et al, 2006;Kim et al, 2007).…”
Section: Environmental Xenoestrogens 421 Industrial Xenoestrogens: mentioning
confidence: 99%
“…BPA can mimic estradiol action in inducing vaginal coalification, uterine vascular permeability, growth and differentiation of the mammary gland and c-fos gene expression in the female reproductive tracts. NP and BPA can reduce function of male gametogenic and accessory reproductive organs, alter the release of pituitary and gonadal hormones, and disrupt sperm production in adult male rates (Boockfor and Blake, 1997;Howdeshell et al, 1999;Kwack et al, 2002).…”
Section: Introductionmentioning
confidence: 99%